When Mindsets Collide: Switching Analytical Mindsets to Advance Organization Science - Zyphur, Michael J. (Academy of Management Review, 2009)
Analytic techniques have associated mindsets that can determine the way scholars conceptualize their objects of study. I propose that switching these "analytical mindsets" can lead to new theoretical insights. Using two examples, I show how switching analytical mindsets allows for divergent, creative thinking that can help researchers generate new theoretical foci. I conclude by discussing the importance of attending to methodology when engaging in the process of theory construction.